Teoretical and practical aspects of conducting research on integration processes and intercultural communication within educational space - Garnyk, Liudmyla Petrivna; Snihurova, Irina Ivanivna; Danchenko, Irina Oleksiivna (Видавнича група "Наукові перспективи", 2023)
Multidimensional aggression of Russian Federation and attempts of occupying Ukrainian territories caused waves of mass migration of population from Eastern and Southern Ukraine to its Western regions or to European Union, where forced refugees have got temporary shelters and favorable conditions for accommodation, also psychological and medical assistance, employment proposals and possibility to continue education into primary, secondary, professional and higher education institutions. The vast majority of teachers and staff members of European educational institutions, where thousands of Ukrainians were sent to continue their studies, had to find solution for issue of finding such a format of work with new students that would simplify their integration into the new sociocultural environment or even facilitate for them more successful assimilation of new learning material. Essential need in practical recommendations for organization of educationalprocess in mixed groups, where Europeans and Ukrainians (foreigners) study together, initiates development of methods on complex diagnostics of educational process participants responsibility for tolerant constructive intercultural communication and their integration into socio-cultural space of new educational institution. Given comprehensive diagnostic technique must meet the following criteria: collection and analysis of information can also be carried out in an interactive and remote mode; methods of data collection and analysis allow to reach the largest (multicultural) audience of respondents and quickly process the results using software; selected data collection methods should contain clearly formed questions that can be translated into other languages without loss of content; obtained diagnostic results can be used both for working with small groups and for developing a program of special measures for pedagogical and socio-psychological support of certain category of foreign students studying in mixed groups. Considering the specifics of main research issues, it was proposed build research methodology using following techniques: diagnostics of general communicative tolerance (V. Boyko); tolerance Index express test (G. Soldatova); types of ethnic self-awareness (G. Soldatova, S. Ryzhova); determination of sociocultural identity (OSKI); scale of a social distance (scale of Еmory Bogardus) (version of L. Pochebut); determination of vital values (MUST-TEST) (P. Ivanov, E. Kolobova), as well as determining the state of adaptation of the individual to the new sociocultural and/or linguistic environment of L. Jankowski. Also article provides an overview of key theoretical foundations and practical aspects ofplanning and conducting psychosocial research on integration processes and intercultural communication within educational space.

Багатопланова агресія Російської Федерації та спроби окупації українських територій спричинили хвилі масової міграції населення зі Сходу та Півдня України до її західних регіонів або до Європейського Союзу, де вимушеним біженцям надавався тимчасовий притулок та створювалися сприятливі умови для їх розміщення, а також надавалася підтримка у вигляді соціальної, психологічної й медичної допомоги, працевлаштування і продовження освіти в мережах закладів початкової, середньої, професійної та вищої освіти. Більшість викладачів та співробітників європейських освітніх закладів, куди було направлено для продовження навчання тисячі українців-шукачів притулку, мали розв'язати питання щодо пошуку такого формату роботи з новими учнями, який би спростив для них інтеграцію до нового мовного й соціокультурного середовища а також сприяв би більш успішному засвоєнню ними нового навчального матеріалу. Нагальна потреба в практичних рекомендаціях щодо організації навчально-виховного процесу в змішаних групах, де разом навчаються європейці та українці (іноземці), започаткувала розробку методики комплексної діагностики здатності учасників навчального процесу дотолерантного конструктивного міжкультурного спілкування й інтеграції до соціокультурного простору нового навчального закладу. Така комплексна методика діагностики повинна відповідати наступим критеріям: збір та аналіз інформації може бути проведено також й у інтерактивно-дистанційному режимі; методи збору та аналізу даних дозволяють охопити якомога більшу (мультикультурну) аудиторію респондентів й швидко обробити результати задопомогою програмного забезпечення; обрані методики збору даних мають містити чітко сформовані запитання, які можна перекласти іншими мовами без втрати змісту; отримані результати діагностики можна застосувати як дляроботи з малими групами, так і для розробки програми спеціальних заходівпедагогічної та соціально-психологічної підтримки певної категорії іноземних здобувачів освіти, які навчаються у змішаних групах. Враховуючи спеціфіку поставленого технічного завдання, було запропоновано використовувати наступні методики, як: діагностика загальної комунікативної толерантності (В. Бойка), експрес-тест Індекс толерантності (Г. Солдатової), діагностика типу етнічної ідентичності (Г. Солдатової та С. Рижової), визначення соціокультурної ідентичності (ОСКІ); шкаласоціальної дистанції Еморі Богардуса (адаптація Л. Почебут); визначення життєвих цінностей MUST-TEST (варіант П. Іванова та Є. Колобової), а також визначення стану адаптації особистості до нового соціокультурного та/або мовного середовища Л. Янковського. Також у статті представлено огляд ключових теоретичних засад й практичних аспектів планування та проведення психосоціальних досліджень інтеграційних процесів і міжкультурної комунікації в освітньому просторі.
Теоретичні та практичні аспекти проведення досліджень інтеграційних процесів і міжкультурної комунікації в освітньому просторі
Keywords: adaptation of foreigners; cross-cultural communication; methodology of sociocultural research; psycho-social rehabilitation of refugees; social distance; integrative pedagogy; Muslim diasporas of Kharkiv city; адаптація іноземців; кроскультурна комунікація; методологія соціокультурного дослідження; психосоціальна реабілітація біженців; соціальна дистанція; інтеграційна педагогіка; мусульманські діаспори міста Харкова